2024
DOI: 10.1186/s40780-024-00331-3
|View full text |Cite
|
Sign up to set email alerts
|

Public hospital pharmacists’ knowledge, attitudes, and practices for antibiotic stewardship implementation in Limpopo Province, South Africa

Tiyani Comfort Mthombeni,
Johanita Riétte Burger,
Martha Susanna Lubbe
et al.

Abstract: Background Hospital pharmacists are important in antibiotic stewardship programs (ASP), a global strategy to combat antibiotic resistance (ABR). South African public hospitals have limited ASP implementation. This study describes Limpopo Provincial Hospital pharmacists’ knowledge, attitudes, and practice toward ASP implementation. Method A questionnaire to explore pharmacists’ knowledge, attitudes and practices regarding ASP implementation comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…In the current study, 163 (90.1 %), 161 (89.0 %) and 128 (70.7 %) of the health professionals believed that AMR was a significant problem both in Ethiopia, worldwide, and in their hospitals respectively. Although there was a slight difference on magnitude, the report was almost similar to a report on health professionals' beliefs at Black Lion Hospital, which showed that antibiotic resistance is a significant problem worldwide (94.6 %), in Ethiopia (91.7 %) and in their hospital (84.5 %) [ 44 ], 93 % of physicians in Cameron perceive that AMR is a nationwide problem [ 72 ], physicians in Nigeria recognize AMR as a global (95.4 %) and local problem (81.1 %) [ 73 ], and in another study in Nigeria among health professionals, 96.0 % of whom believed that antibiotic resistance was a problem in Nigeria, 84.0 % agreed that AMR was a problem for their practice [ 46 ] but in Ghana very few physicians perceived antibiotic resistance as global problem (30.1 %), national problem (18.5 %), and problem in their hospital (8.1 %) [ 74 ]. In South Africa, 78.5 % of pharmacists perceived that AMR was a problem in their hospitals [ 75 ], and in Zambia, 95 % of health professionals perceived AMR as a current problem in their practice [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, 163 (90.1 %), 161 (89.0 %) and 128 (70.7 %) of the health professionals believed that AMR was a significant problem both in Ethiopia, worldwide, and in their hospitals respectively. Although there was a slight difference on magnitude, the report was almost similar to a report on health professionals' beliefs at Black Lion Hospital, which showed that antibiotic resistance is a significant problem worldwide (94.6 %), in Ethiopia (91.7 %) and in their hospital (84.5 %) [ 44 ], 93 % of physicians in Cameron perceive that AMR is a nationwide problem [ 72 ], physicians in Nigeria recognize AMR as a global (95.4 %) and local problem (81.1 %) [ 73 ], and in another study in Nigeria among health professionals, 96.0 % of whom believed that antibiotic resistance was a problem in Nigeria, 84.0 % agreed that AMR was a problem for their practice [ 46 ] but in Ghana very few physicians perceived antibiotic resistance as global problem (30.1 %), national problem (18.5 %), and problem in their hospital (8.1 %) [ 74 ]. In South Africa, 78.5 % of pharmacists perceived that AMR was a problem in their hospitals [ 75 ], and in Zambia, 95 % of health professionals perceived AMR as a current problem in their practice [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, health professionals believed that easy access to antibiotics without a prescription 155 (85.6 %), inappropriate consumption of antibiotics 137 (75.7 %), lack of adequate surveillance for drug-resistant organisms 127 (70.2 %) and adequate staff education regarding antibiotic consumption and resistance 124 (68.5 %), and overuse of antibiotics due to a lack of diagnostic tests 119(65.7 %) were perceived as key contributors to AMR in hospitals. This was similar to the study in Black Lion Hospital, which reported 84.3 % agreement with easy access to antibiotics, 82.0 % inappropriate consumption, and 64.4 % lack of adequate diagnostic tests as the main perceived causes of AMR [ 44 ] and in Ghana overuse of antibiotics in hospitals (67.5 %), uncompleted antibiotic therapy were common causes for AMR (50.31 %) and poor quality of antibiotics (37.7 %) [ 74 ]. In Uganda, antimicrobial overuse at hospitals (91 %), poor infection control practices by health professionals (79 %), and prescribing broad-spectrum antimicrobials when equally effective narrower-spectrum antimicrobials are available (73 %), were perceived causes for AMR [ 70 ], and in Cameron, physicians perceived that inappropriate use of antibiotics (94 %), overuse of antibiotics (87 %), and indiscriminate use of broad-spectrum antibiotics (71 %), were possible causes for AMR [ 72 ].…”
Section: Discussionmentioning
confidence: 99%